2012
DOI: 10.1128/jvi.01166-12
|View full text |Cite
|
Sign up to set email alerts
|

Entry of Influenza A Virus with a α2,6-Linked Sialic Acid Binding Preference Requires Host Fibronectin

Abstract: The receptor binding specificity of influenza A virus is one of the major determinants of viral tropism and host specificity. In general, avian viral hemagglutinin prefers to bind to α2,3-linked sialic acid, whereas the human viral hemagglutinin prefers to bind to α2,6-linked sialic acid. Here, we demonstrate that host fibronectin protein plays an important role in the life cycle of some influenza A viruses. Treating cells with anti-fibronectin antibodies or fibronectin-specific small interfering RNA can inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 52 publications
1
43
1
Order By: Relevance
“…While some studies have found a correlation between receptor binding and IAV virulence18212226, there is growing evidence that the HA binding to SA-containing receptors does not always correlate with infection in itself373839404142. Consistent with the latter and our previous observation that variations in SA binding by H3N2 IAVs isolated from 1968 to 2012 does not correlate with disease severity or spread13, modulation in receptor binding of rgHK68 viruses had no effect on such viral characteristics as elution from turkey RBC, growth in epithelial cell cultures, cytopathology, or virulence in mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While some studies have found a correlation between receptor binding and IAV virulence18212226, there is growing evidence that the HA binding to SA-containing receptors does not always correlate with infection in itself373839404142. Consistent with the latter and our previous observation that variations in SA binding by H3N2 IAVs isolated from 1968 to 2012 does not correlate with disease severity or spread13, modulation in receptor binding of rgHK68 viruses had no effect on such viral characteristics as elution from turkey RBC, growth in epithelial cell cultures, cytopathology, or virulence in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the latter and our previous observation that variations in SA binding by H3N2 IAVs isolated from 1968 to 2012 does not correlate with disease severity or spread13, modulation in receptor binding of rgHK68 viruses had no effect on such viral characteristics as elution from turkey RBC, growth in epithelial cell cultures, cytopathology, or virulence in mice. One possible explanation for this may be a role for post-attachment factors373839404142. Another possibility is that H3N2 binding and entry is mainly dependent on only a limited subset of sialylated glycans, and that binding to these biologically critical ligands has remained relatively constant over time.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of fibronectin in influenza virus infection was demonstrated in a study by Leung et al 52 . It was identified as a key entry factor specifically required for viruses with a tropism for glycoproteins with α(2,6)-linked sialic acid (SA) moieties.…”
Section: Fibronectinmentioning
confidence: 92%
“…4). The human influenza virus strain WSN, which recognizes a2,6-linked sialic acid (Leung et al, 2012), was also inhibited by Streptococcus suis wt. By contrast, the mouse-adapted H1N1 virus PR8, which recognizes a2,3-linked sialic acid (Koerner et al, 2012; Tate et al, 2011), was not inhibited in its HA activity by Streptococcus suis wt (Fig.…”
Section: Encapsulated Streptococcus Suis Inhibits Ha Activity Of Diffmentioning
confidence: 99%